Seeds and vegetative propagules of all selected invasive plants in Europe do not survive industrial composting - Sabina Tomše; Marjeta Resnik; Nejc Gorjan; Simona Strgulc Krajšek (NeoBiota)
Plant material of invasive alien plant species (IAPS) must be appropriately disposed of to prevent unintended spread. The current guidelines in Slovenia and in several other European countries recommend composting only the parts of the plants from which they cannot sprout and reproduce. At the same time, the vegetative propagules and seeds should be incinerated. We tested whether the seeds and vegetative propagules (rhizomes, stolons, tubers, and branches) of 30 selected IAPS survive industrial composting, which is the method of processing collected organic waste and green cut from parks and gardens. Mature seeds and vegetative propagules were packed in metal boxes, which were filled with compost and included in the hygienisation phase of biowaste processing at the Regional Waste Management Centre, RCERO Ljubljana. After the industrial composting for 17 days, seed germination and viability tests were done and compared with a control group of seeds collected from the same plants but not undergoing the composting process. The composted and fresh vegetative propagules were planted in pots with soil, and the number of rooted parts was counted. None of the seeds and the vegetative propagules survived the industrial composting process, and we can conclude that it is safe to dispose of the IAPS like other organic waste or green cut.